Kontroversi seputar Kedudukan Basmalah: Studi Analisis Ma'tsurat Tafsir: The Controversy Surrounding the Status of the Basmalah: An Analytical Study of Ma'thurat Tafsir - H. Mawardi Abdullah (Fenomena, 2004)
The status of the Basmalah in the Quran, particularly whether it is an integral part of Al-Fatihah and other surahs, has sparked enduring controversy among Muslim scholars, with significant theological and practical implications for ritual prayer. This debate is rooted in conflicting prophetic traditions (ma'tsurat) that either affirm or deny the Basmalah as a verse of Al-Fatihah. This study aims to critically examine the authenticity of these conflicting hadiths to clarify the basis of the juristic disagreement. Using a qualitative library research method, this study analyzed the chains of transmission (sanad) and texts (matan) of relevant hadiths found in the Kutub al-Tis'ah (nine major hadith collections). The findings reveal that all primary narrators in the analyzed chains are deemed trustworthy (tsiqah) and that the sanads are continuous (mutasil), suggesting that both sets of conflicting hadiths are authentically attributed to the Prophet Muhammad. Consequently, the opposing opinions on the Basmalah are supported by equally strong evidence. The study concludes that this issue must be recognized as a legitimate khilafiyah (jurisprudential difference of opinion) and recommends fostering a tolerant attitude that allows Muslims the freedom to follow their preferred scholarly opinion, thereby transforming potential conflict into a source of merciful diversity. Kedudukan Basmalah dalam Al-Qur'an, khususnya apakah ia merupakan bagian integral dari surat Al-Fatihah dan surat lainnya, telah memicu kontroversi berkepanjangan di kalangan ulama, dengan implikasi teologis dan praktis yang signifikan dalam ibadah shalat. Perdebatan ini berakar pada tradisi kenabian (ma'tsurat) yang saling bertentangan, baik yang mengafirmasi maupun menolak Basmalah sebagai ayat Al-Fatihah. Penelitian ini bertujuan untuk mengkaji secara kritis otentisitas hadis-hadis yang tampak kontradiktif tersebut guna memperjelas dasar perbedaan mazhab. Menggunakan metode penelitian kepustakaan kualitatif, penelitian ini menganalisis rantai transmisi (sanad) dan teks (matan) hadis-hadis terkait yang terdapat dalam Kutub al-Tis'ah. Temuan penelitian menunjukkan bahwa seluruh perawi utama dalam rantai yang dianalisis dinilai terpercaya (tsiqah) dan sanadnya bersambung (mutasil), mengindikasikan bahwa kedua himpunan hadis yang kontradiktif tersebut secara otentik bersumber dari Nabi Muhammad. Konsekuensinya, pendapat yang berlawanan tentang Basmalah sama-sama didukung oleh bukti yang kuat. Penelitian ini menyimpulkan bahwa persoalan ini harus diposisikan sebagai khilafiyah yang sah, dan merekomendasikan pengembangan sikap toleran yang memberikan keleluasaan kepada umat Islam untuk memilih pendapat yang diyakininya, sehingga perbedaan pendapat berubah menjadi rahmat yang membawa kebaikan.